Asthma, allergy, and atopy in three south-east Asian populations. Issue 12 (December 1994) - Leung, R; Ho, P
Abstract : BACKGROUND–Whilst many recent reports have suggested a rise in the prevalence of asthma and allergic disease in Western countries, little is known about the epidemiology of these common conditions in south-east Asia. This study compared the prevalence of asthma and allergic disease amongst secondary school students in three south-east Asian populations–Hong Kong, Kota Kinabalu in Malaysia, and San Bu in China–and investigated the associations with atopy and family history. METHODS–Secondary school students were given standard questionnaires on respiratory and allergic symptoms for completion by parents with response rates of 89.2% in Hong Kong (611 male, 451 female; mean (SD) age = 13.9 (1.8 years), 87.6% in Kota Kinabalu (134 male, 275 female; 15.5 (2.1) years), and 98.6% in San Bu (492 male, 245 female; 16.4 (1.8) years). Skin tests were performed in a subsample of students to determine atopic status. RESULTS–The respective prevalence (and 95% CI) for hayfever, eczema, and wheeze or asthma were 15.7% (13.5, 17.9), 20.1% (17.7, 22.5), 11.6% (9.3, 13.9) in Hong Kong, 11.2% (8.2, 14.3), 7.6% (5.0, 10.1), 8.2% (5.5, 10.9) in Kota Kinabalu, and 2.1% (1.2, 3.1), 7.2% (5.4, 9.1), 1.9% (0.7, 3.1) in San Bu. Atopy was common and was present in 49.0-63.9% of subjects in the three populations. Dust mite and cockroach were the commonest allergens that gave positive reactions in 42.8-60.5% and 25.7-35.9% of students respectively. A higher proportion of students in Hong Kong had severe degree of reactivity on skin test than the other two populations. Family history was associated with asthma and allergic symptoms in the three populations conferring a 3-80-fold increase in risk to family members and was a stronger predictor for asthma and allergy than atopy. CONCLUSIONS–Prevalence of asthma and allergic disease is low compared with Western countries, but considerable differences exist between the three south-east Asian populations despite similar rates of atopy. Asthma and allergic disease are more strongly associated with family history than atopy, which suggests that genetic and environmental factors common to the family, other than aeroallergen sensitisation, are important in the pathogenesis of asthma and allergy in the region.